14. Analisis Penilaian Pembelajaran PAI Pada Anak Berkebutuhan Khusus - Meisya Adinda; Dede upendi (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
The aim of the research is to find out how the learning assessment of Children with Special Needs, especially in Islamic Religious Education (PAI) subjects. The method in this study uses a qualitative method with the type of library search and data collection techniques, namely analyzing from previous research and journals, books or other articles related to the research title. The results of this study are that the assessment of Islamic Religious Education (PAI) learning for Children with Special Needs is the same as the assessment in general, namely following government regulations from the education office. Which consists of cognitive, affective and psychomotor domains.